Price pass-through of CO₂ costs - Barbara Breitschopf; Meta Thurid Lotz; Frank Marscheider-Weidemann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
The price pass-through of CO2 costs was analysed for HRC and PE/PP products as parts of a BEV. It was revealed that the feasibility of transferring these costs hinges on a company's ability to dictate prices, either as a significant player in international markets or through bilateral agreements. While the data and information gathered shed light on the complexity of business relationships and markets, it unequivocally demonstrates that the question of price pass-through is far from being answered straightforward. Low transparency about various business relations and markets, lack of information on specific production volumes, inputs, and current cost and pricing data were identified as critical hindrances to assessing the pass-through of prices, despite the existence of scientific concepts. Within the industry, a few companies may possess a strong foothold in the global market and be equipped to navigate elevated costs without external intervention, whereas others may lack the means to offset cost increases due to CO2 prices. Policymakers are thus faced with the challenge of formulating targeted policies for less competitive companies and industries expected to lose market shares due to CO2 pricing, while refraining from interfering with those capable of robust market competition. In essence, the domestic imposition of CO2 pricing poses a significant threat to the price competitiveness of the domestic carbon-intensive industry. A welldesigned CBAM is imperative, yet its effectiveness on global prices also hinges on whether global producers are subject to CO2 emission costs. Should global producers remain unaffected by such expenses, many European producers are likely to encounter a general cost disadvantage when exporting to the international market.
Keywords: 330; competitiveness; CO2 prices; chemical and steal industry